Sustainability and Transformation of Station Street, Isparta: A Study of Housing Development and Lifestyles Across Time - AKDAĞ, Nurcihan; Beyhan, Şefika Gülin (EMARA: Indonesian Journal of Architecture, 2025)
Rapid urbanization, often accompanied by unplanned changes that undermine ecological balance and social cohesion, has led to an increased emphasis on the development of sustainable cities. Station Street in Isparta, which was established in 1936 with the construction of the Station Building, is an example of how zoning regulations, modernization, and changing housing typologies have challenged both the urban landscape and human activity. It was an effort to study the morphological, social and cultural changes in Station Street from a sustainability perspective. A qualitative approach was taken, based on archival research of zoning laws and development plans, field observations, spatial analyses, and oral history interviews with residents who had lived in the area for many years. Evidence from the study showed that there was a distinct transition from individual detached garden houses to bulky reinforced concrete apartments and ultimately to dense multi-storey blocks, supported by 1967 (seven year plan) for zoning and condominium law. Despite the expansion of housing and the introduction of mixed-use functions, these modifications also led to the disappearance of green spaces, the division of neighborhoods, and ultimately the erosion of the street's significance as a cultural and economic center. Additionally, Morphological change was associated with social and cultural loss, which was highlighted in oral histories as the decline of neighborhood practices and identity. Based on the three-pillar sustainability model, the study concludes that Station Street's path was aimed at modernization but not ecological or social resilience